Discovery of an algicidal compound from Brevibacterium sp. BS01 and its effect on a harmful algal bloom-causing species, Alexandrium tamarense - An, Xinli; Zhang, Bangzhou; Zhang, Huajun; Li, Yi; Zheng, Wei; Yu, Zhiming; Fu, Lijun; Zheng, Tianling (Frontiers in Microbiology, 2015)
Blooms of the dinoﬂagellate Alexandrium tamarense have become worldwide phenomena and have detrimental impacts on aquatic ecosystems and human health. In this study, a culture supernatant of the marine actinomycete BS01 exerted a strong algicidal effect on A. tamarense (ATGD98-006). The target algicide from BS01 was separated by adsorption chromatography and identified by MALDI-TOF-MS and NMR analysis. The results suggested that the purified algicidal component corresponded to a hydrophobic compound (2-isobutoxyphenyl)amine (C10H15NO) with a molecular weight of 165 Da, which exhibited a significant algicidal effect (64.5%) on A. tamarense. After incubation in 5 μg/mL of (2-isobutoxyphenyl)amine for 24 h, the algae lost mobility and sank to the bottom of the flasks, and 56.5% of the algae cells lost vitality at a concentration of 20 μg/mL (p < 0.01) despite having intact cell profiles. Morphological analysis revealed that the cell structure of A. tamarense was altered by (2-isobutoxyphenyl)amine resulting in cytoplasm degradation and the loss of organelle integrity. The images following propidium iodide staining suggested that the algal nucleus was also severely damaged and eventually degraded due to exposure to the algicidal compound. All of the results indicate that (2-isobutoxyphenyl)amine from the actinomycete might be a candidate for the control of bloom-forming A. tamarense.